Tetrathiafulvalene as an electron acceptor for positive charge induction on the surface of silver nanoparticles for facilitated olefin transport - Choi, Hyungwoo; Lee, Jung Hyun; Kim, Young Rae; Song, Donghoon; Kang, Sang Wook; Lee, Sang Soo; Kang, Yong Soo (ROYAL SOC CHEMISTRY, 2014)
Tetrathiafulvalene (TTF), a well-known electron donor, can also behave as an electron acceptor after being adsorbed on the surface of silver nanoparticles (Ag NPs), thereby inducing a partial positive charge on the Ag NPs surface. The Ag NPs activated by TTF help propylene transport much faster than propane, i.e., facilitated olefin transport, resulting in extremely high separation performance for propylene-propane mixtures.
Keywords: ENERGY-LEVEL ALIGNMENT; ORGANIC/METAL; METAL